Diseño y evaluación de un programa de lenguaje asociativo (climco) para personas adultas diagnosticadas con trastorno del espectro autista nivel 1: un estudio de caso (2017)
This is a quantitative research, with a non-experimental methodological design, descriptive transactional, case study. This thesis was made the application of a virtual program called CLIMCO, which was designed for the exercise of associative language in four adults diagnosed with autism spectrum disorder Level 1. Taking into account that one of the main characteristics of this disorder is the inability to master the language in terms of the extraction of meanings and its use for communicative purposes, the program was evaluated through the pre-test/Post test application of the verbal Comprehension Index (ICV) of the adult Wechsler Intelligence Scale-IV (WAIS IV), using the vocabulary subtests , similarities and information; Which allow to account for semantic and pragmatic elements in the language of people. The results of each of the participants reveal better scores in the application of the post-test and improvement in the last application of the program.